2007
DOI: 10.1007/s00417-006-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Chorioretinal anastomosis and photodynamic therapy:a two-year follow-up study

Abstract: AMD eyes with chorioretinal anastomosis can benefit from PDT with Verteporfin at two years. However, during the second year significant additional VA loss occurs mainly due to recurrence. New modalities of treatment are necessary to achieve VA improvement in CRA eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…The prevalence of RAP is higher than expected [14,15,16,17] and this may contribute to a higher rate of CNV development. In fact, patients with RAP are believed to have a much higher risk of developing bilateral lesions than patients with other forms of neovascularization – 100% at 3 years [15,16,18]. The fact that no eyes developed polypoidal choroidal vasculopathy is of relevance and may be due to the fact that every patient included had clear evidence of a large central scar in the non-study eye due to CNV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of RAP is higher than expected [14,15,16,17] and this may contribute to a higher rate of CNV development. In fact, patients with RAP are believed to have a much higher risk of developing bilateral lesions than patients with other forms of neovascularization – 100% at 3 years [15,16,18]. The fact that no eyes developed polypoidal choroidal vasculopathy is of relevance and may be due to the fact that every patient included had clear evidence of a large central scar in the non-study eye due to CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Hot spots are observed frequently in RAP, polypoidal choroidal vasculopathy and focal occult CNV [14]. Plaques are larger than 1 disk diameter in size and may be associated with non-active areas of neovascularization [18,19]. ICG may demonstrate neovascular connections between the choroid and retina, in the form of anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fellow eye is at high risk of developing RAP (Gross et al 2005). Various treatments for RAP, such as conventional laser photocoagulation (Slakter et al 2000;Johnson & Glaser 2006), photodynamic therapy (PDT) (Boscia et al 2004;Panagiotidis et al 2006;Silva et al 2007), surgical therapy (Borrillo et al 2003;Sakimoto et al 2005;Shiragami et al 2007) or combined therapies (Boscia et al 2005;Nakata et al 2006), have been discouraging or showed limited success with recurrent exudation. Recent studies showed that combined therapy of intravitreal triamcinolone and PDT effectively reduced angiographic leakage and had a positive effect on visual acuity (Freund et al 2006;van de Moere et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The therapy strategies used in the past were numerous and included conventional laser photocoagulation [11,12], photodynamic therapy [13][14][15], surgery [16][17][18][19] or combinations [16,20], all with more or less discouraging outcomes.…”
Section: Introductionmentioning
confidence: 99%